The Language of Warning: The World Scientists’ Efforts to Communicate and the Challenge of Poignancy - Scott Slovic (Ecocene: Cappadocia Journal of Environmental Humanities, 2020)
It’s one thing to issue a clarion cry (or multiple clarion cries), and yet another thing to be heard. The world scientists’ warnings about the direness of our climate predicament have offered detailed, authoritative information about the condition of the planet, but they fall short in the critical area of poignancy. The recent warnings are not the first of their kind—prominent climate scientists have been issuing such documents for decades. And yet even as scientists’ knowledge of planetary systems has become more refined, their attentiveness to the language of warning—and what works and what doesn’t—has not progressed noticeably. Psychologists, communication specialists, and humanities scholars in various disciplines (creative writing, literary studies, philosophy) have long noted that humans are vulnerable to psychic numbing when inundated with abstract information, particularly when this information concerns large-scale phenomena—this includes global climate change. While recognizing the importance of the world scientists’ efforts to evoke an “emergency response,” this article attempts to warn against warnings that do not heed the psychological realities of how the human mind processes data. It is important to calibrate warnings to the sensitivities and insensitivities of human readers. The public cannot heed what it cannot hear